World News - Refuge Editor (Refuge: Canada’s Journal on Refugees, 1983)
The Statue "Refugee" by the Argentinian Sculptor, Adolfo Perez Esquivel, who was awarded the Nobel Peace Prize in 1980, was unveiled on December 13, 1982 at the headquarters of the office of the United Nations High Commissioner for Refugees in Geneva.